Experimental Mathematics. Volume 16, Number 4, 2007 - A K Peters (A K Peters, 2009)
Elliptic Curves as Attractors in ℙ2 Part 1: Dynamics Full TextPDF (2.0 MB) Authors Araceli Bonifant, Marius Dabija and John Milnor 385-420 No access to content An Explicit Formula for the Arithmetic–Geometric Mean in Genus 3 Full TextPDF (680.8 KB) Authors D. Lehavi and C. Ritzenthaler 421-440 No access to content On the Singularization of the Two-Dimensional Jacobi–Perron Algorithm Full TextPDF (432.0 KB) Author B. Schratzberger 441-454 No access to content Lenstra's Constant and Extreme Forms in Number Fields Full TextPDF (242.3 KB) Authors R. Coulangeon, M. I. Icaza and M. O'Ryan 455-462 No access to content Constructing Hyperbolic Polyhedra Using Newton's Method Full TextPDF (2.1 MB) Author Roland K. W. Roeder 463-492 No access to content Sparse Representation for Cyclotomic Fields Full TextPDF (218.1 KB) Author Claus Fieker 493-500 No access to content The Propositional Theory of Closure Full TextPDF (245.8 KB) Authors A. E. McCluskey, D. W. McIntyre and W. S. Watson